Identification of QTL for locomotor activation and anxiety using closely-related inbred strains - Bailey, Janice S. (2008)
We carried out a QTL mapping experiment in two phenotypically similar inbred mouse strains, C57BL/6J and C58/J, using the open field assay, a well-established model of anxiety-related behavior in rodents. This intercross was initially carried out as a control cross for an ENU-mutagenesis mapping study. Surprisingly, although open field behavior is similar in the two strains, we identified significant QTL in their F2 progeny. Marker regression identified a locus on chromosome 8 having associations with multiple open field measures and a significant interaction between loci on chromosomes 13 and 17. Together, the chromosome 8 locus and the interaction effect form the core set of QTL controlling these behaviors with additional loci on chromosomes 1 and 6 present in a subset of the behaviors.